Physical, anthropometric, and athletic movement qualities discriminate development level in a rugby league talent pathway - Pearce, L. A.; Sinclair, W. H.; Leicht, A. S.; Woods, C. T. (The Journal of Strength and Conditioning Research, 2018)
This study compared the physical, anthropometric, and athletic movement qualities of talent-identified rugby league (RL) players within a development pathway. From a total of 174 players, 3 developmental levels were defined: under 18 (U18; n = 52), under 20 (U20; n = 53), and state league (SL; n = 69). All players performed a test battery that consisted of 5 physical assessments, 2 anthropometric measurements, and an athletic movement assessment. A multivariate analysis of variance modeled the main effect of developmental level (3 levels: U18, U20, and SL) on test criterion variables. Receiver-operating characteristic (ROC) curves were then built for the criterion variables that showed a significant developmental level effect. A significant effect was noted (V = 0.775, F = 5.43, p = 0.05), with the SL players outperforming their U18 and U20 counterparts for measures of body mass, peak and average lower limb power, double lunge (left side), single-leg Romanian deadlift (left and right sides), the push-up, and total athletic ability assessment score (p = 0.05; d = 0.35-1.21). The ROC curves generated an area under the curve of greater than 65% for each test criterion, indicating greater than chance discrimination. These results highlight the physical, anthropometric, and athletic movement qualities discriminant of development level within a RL talent pathway. Practitioners are encouraged to consider the thresholds from the ROC curves as an objective guide to assist with the development of physical performance qualities that may augment player progression in Australian RL.